Casino Self-Exclusion Programmes: A Review of the Issues - Nowatzki, Nadine R.; Williams, Robert J. (Taylor & Francis, 2002)
Casino self-exclusion is a procedure by which individuals can have themselves banned from entering a casino. One of the purposes of this paper is to present information about the availability and features of these programmes. A second purpose is to make recommendations about how to best operate them based on cross-jurisdictional analysis and lessons from the addiction literature. The first section of the paper describes the typical casino self-exclusion programme, outlining the features common to most policies. The second section provides a detailed overview of the programmes operating in Canada in order to give the reader an appreciation of the procedural variations that exist. The third section discusses the effectiveness of self-exclusion programmes. Finally, the fourth section contains recommendations on ways to improve effectiveness. When properly implemented, self-exclusion can be a valuable tool in helping to curb problem gambling.
Permission to archive accepted author manuscript
Keywords: Casinos; Gambling Policy; Gambling Prevention